MOVE! multidisciplinary programs: Challenges and resources for weight management treatment in VHA - Rosenberger, Patricia H (Springer-Verlag, 2011)
The MOVE! program has been a successful weight management and physical activity initiative from the Veteran's Health Administration. While it embraces a multicomponent approach to weight management, local facilities have primarily focused on the implementation of delivery of MOVE! educational materials to groups or individuals. We discuss additional MOVE!-related weight management efforts within VHA that reflect treatment strategies beyond delivery of these educational materials. First, we present a case study that highlights the special challenges associated with the Veteran overweight/obese population. Second, we describe the implementation of our local, multidisciplinary, individualized weight management clinic as an example of on-the-ground provision of a higher treatment intensity program as part of MOVE!'s multicomponent model. Third, we present program outcomes and consider challenges to program sustainability.